The Rise of the Imperial Museum - Shaw, Wendy (Possessors and Possessed, 2003)
After the initial efflorescence of the dual collections in the former Church of Hagia Irene, the archaeological antiquities came to the fore as the military antiquities received less attention and finally, in 1877, were closed to the public. Why did the Ottoman museum shift its attention from a military to a Helleno-Byzantine heritage at this juncture? There were two primary reasons. First, the new constitution enacted soon after Sultan Abdülhamid II acceded to the throne allowed for broader inclusion of cultures under the Ottoman umbrella, which could be facilitated by an emphasis on antiquities. Second, the celebration of military history